First Responders Field Trials of Saliant Technology - Anton Osvald; Maria Luskova; Markku Parviainen; Mika Rasanen; Jozef Svetlik; Jaroslav Flachbart; Miroslava Vandlickova; Vladimir Mozer (Communications - Scientific letters of the University of Zilina, 2015)
SALIANT - Selective Antibodies Limited Immuno Assay Novel Technology is the title of the research project developed and realised by a European consortium of biotechnology companies, universities and government forensic laboratories within the Seventh Framework Programme (FP7), Security Theme. The aim of this project was to develop a hand-held device for real-time analysis of trace levels of explosives, chemicals and drugs. The key innovation was a positive detection lateral-flow test for small molecules that is rapid, highly sensitive and simple to use making it ideally suited to deployment by First Responders and Forensic Service Providers at crime scenes and terrorist incidents. The Faculty of Special Engineering of the University of Zilina (FSE) as a project team member, was responsible for the task of evaluating the efficacy and sensitivity of the SALIANT technology for explosives detection for emergency responders’ use. This paper provides the results and details about conducted experiments for the TNT explosive which were carried out in real-world conditions. The trials were specifically oriented on verification of the explosion products coverage and possibilities of their measuring by the SALIANT system.